Relationship between scientific reasoning skills and mathematics achievement among Malaysian students - Nor’ain Mohd. Tajudin,; Mohan Chinnappan, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The role of reasoning in mathematical performance is a continuing topic of interest for researchers in mathematics education. This present study explored the link between scientific reasoning skills and mathematics performance as measured by students’ responses to a series of novel problems. Results indicated the existence of a moderate positive correlation between the two variables. All participating students exhibited low levels of scientific reasoning. Despite this, students in the high-achievement group performed significantly better than their peers in the lowachievement group in the mathematics test. The results suggest that while scientific reasoning is necessary, these set of skills may not fully explain the kind of reasoning that underpins mathematical problem solving among Malaysian secondary students. We draw implications for instructions to support the development and use of reasoning in mathematical learning in Malaysian classrooms.